(I)materialidades da arquitectura contemporânea - Mariana Teixeira Pascoal Simões (2009)
The present work begins by discussing in the first chapter the material evolution of Architecture, having in mind the theme of technology and the body. Technology is considered to be a key element that mediates and catalyzes material transformation in the fields of architecture and art, while the body acts as an immaterial or/ and material entity which is capital to analyse and understand space. At the same time, in order to comprehend the current materiality, the idea of contemporary body is introduced through the image of the cyborg body: a fragmented, dynamic and mutant body. There are some concepts that help to clarify this subject, such as genotype body - a body related with information, existing in a virtual level -, and phenotype body - a physical body related with flesh and matter. In the second chapter the concepts of genotype and phenotype act as a metaphor for an approach and analysis of different kinds of materiality: a type of "immateriality" related with synthetic and virtual environments apart from reality; a type of materiality that connects the physical body and actual construction with the potential of new technologies in terms of interaction and performance; a type of materiality whose tectonic counters the ephemeral qualities of the digital, either by having a primitive or minimal attitude towards matter, or by using a large range of exuberant material. The third chapter, regarding the study case of marcosandmarjan, puts together some of the previously analysed aspects like the digital practices, the actual sensory experience of the materials, the interactivity and connectivity, by considering a body related to the biological and technological subjects. Paradoxically, there are some other closer examples confronting these prospective investigations that raise the same kind of questions although using different material resources. The present reflection concludes that the contemporary materiality is envisaged as an extension of the body and revised in a performance condition that can take several directions: the ones of interaction, communication or the answer to the dynamic demanding of a body that inhabits the contemporary world, being those demands whether artistic or functional. We cannot deny the importance of the technique in the materiality having already predicted a wide range of exciting possibilities; however, the difficulty of access to those resources is no excuse to abandon the search.